Developing Students' Potential Skills Through the Implementation of Educational Activities Outside the School Environment in the Post-Pandemic Era - Yunitun Tamara; Syahrial A; Muhammad Zuhdi; Dian Wijaya Kurniawidi; Syamsuddin, Syamsuddin; Kormil Saputra; Rahmatun Inayah; Ika Umratul Asni Aminy; Adella Ulyandana Jayatri (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Community service in Narmada Village, West Lombok, aimed to improve the quality of science and technology literacy learning through a contextual and educational approach. These activities included teaching practices using simple teaching aids, training in developing locally-based Lesson Plans (RPPs), and digital image security education using the SCBIE encryption algorithm. Results showed significant improvements in students' understanding of science concepts and active participation, as well as teachers' skills in designing relevant RPPs. Furthermore, an understanding of the effectiveness of the SCBIE algorithm was gained, with the use of a single key yielding higher e-RMS values, indicating a stronger encryption level. A comparison of the performance of algorithms A and B was also discussed during the training, emphasizing the importance of balancing speed, accuracy, and memory efficiency in implementing image cryptography. This activity significantly contributed to improving educational capacity and digital literacy at the village level.